The Impact of Stakeholder Behavior on the Optimization of Digitalization in the Moroccan Agricultural Supply Chain: A PLS-Based Verification - neggaoui, imane; Lemfarreg, Lamyaa; Yaouhi, Mohamed (Journal of Agricultural Sciences (Belgrade), 2025)
Digital transformation is increasingly recognized as a strategic lever to enhance the logistical performance of agricultural supply chains, particularly in emerging economies. This study investigates the effect of actors' behavior on the optimization of digitalization, by analyzing the relationship between human usage patterns, data storage and processing capacity, and agricultural logistics performance. A conceptual model based on the Diffusion of Innovation Theory and the Dynamic Capabilities Theory was tested using the PLS-SEM method on a sample of 308 stakeholders from the Moroccan agricultural sector. The findings reveal that actors' behavior significantly influences digital capacity, which in turn affects several performance dimensions, including cost reduction, quality improvement, efficiency, competitiveness, and the reduction of intermediary roles. The study emphasizes that human behavior remains central to any digital transformation, and that the success of digitalization projects depends not only on technological tools but also on user practices and interactions. The proposed model offers practical insights applicable to other low-digital-maturity logistics contexts.
Keywords: Digitalization, Agricultural logistics, Stakeholder behavior, Logistics performance